Exploring The Determinants of The Learning Management System (LMS) Quality of Use in TVET Institutions - Mahat, Jazihan; Ismail, Norhafizah; Ghazali, Norliza; Habibi, Akhmad (Journal of Technical Education and Training, 2024)
Learning Management Systems (LMS) have emerged as a vital tool in the modern educational landscape by providing a platform for seamless teaching and learning experiences. However, the factors influencing LMS quality of use remain under-explored, particularly in TVET settings. This study aims to explore the factors influencing the quality of LMS use with an emphasis on three key dimensions: information, system, and service quality. The study draws on the Theory of Reasoned Action (TRA), Technology Acceptance Model (TAM), Social Cognitive Theory, Diffusion of Innovations Theory, and DeLone and McLean Information System Success Model by incorporating constructs such as compatibility, application self-efficacy, subjective norm, technological complexity, perceived usefulness, and perceived ease of use. The data was analysed using structural equation modelling (SEM) on a sample of 372 students from Malaysian Polytechnic institutions. The findings indicated compatibility, subjective norm, technological complexity significantly influence perceived usefulness and perceived ease of use. Application self-efficacy was observed to have a significant effect on perceived ease of use, but not on perceived usefulness. Perceived usefulness and perceived ease of use demonstrated a significant relationship on the LMS quality of use. This study highlights the various factors of LMS quality of use, providing useful insights for stakeholders seeking to improve the utilisation of LMS in academic settings, especially in TVET environments.